2014
DOI: 10.21608/jpp.2014.55427
|View full text |Cite
|
Sign up to set email alerts
|

Types of Gene Action and Hybrid Vigour for Yield and Quality Traits of Melon (Cucumis Melo, L.).

Abstract: This study was carried out in two successive summer seasons (2012 and 2013), at the Experimental Farm of Research Station, Qanater El-Khairya, El-Kalupia Governorate, Agriculture Research Center. The main objectives of this investigation were to estimate of magnitude of additive and non-additive gene effects for some traits in an attempt to stablish some inbred lines. The study also aimed to estimate heterosis degree, relative to mid, better parents and the standard cultivar to determine the hybrid vigour for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…Negative recorded magnitudes of potence ratio indicated the presence of different degrees of recessiveness. These results are consistent with those obtained by Hatem et al (2014)…”
Section: Magnitude Of Heterosissupporting
confidence: 93%
See 1 more Smart Citation
“…Negative recorded magnitudes of potence ratio indicated the presence of different degrees of recessiveness. These results are consistent with those obtained by Hatem et al (2014)…”
Section: Magnitude Of Heterosissupporting
confidence: 93%
“…Barros et al (2011) found that TSS, number of fruits, total yield traits was controlled by additive and dominance effects, on the other side, fruit flesh thickness, fruit diameter and average fruit weight traits were governed by additive effects. Hatem et al (2014) reported that additive and non-additive gene effect was involved while the additive gene effect expressed to play the major role in the inheritance of studied traits. Chaudhary et al (2017) found that, with genetic analysis of total yield and related traits by the diallel mating design on melons and exhibited the characters of fruit flesh thickness, fruit length and average fruit weight.…”
Section: Introductionmentioning
confidence: 99%
“…In cantaloupe, all studied crosses exhibited significantly positive SCA effects for total yield (Hussein and selim, 2014). Hatem et al (2014) on melon found that both additive and non-additive gene effects were involved while the additive gene effects appeared to play the main role in the inheritance of all studied traits. Since estimated GCA: SCA ratio values ranged from 4.4 to 57.8.…”
Section: Introductionmentioning
confidence: 97%